Aspek Epistemologi Inovasi dalam Manajemen Pendidikan Islam - Sarnoto, Ahmad Zain (Indo-MathEdu Intellectuals Journal, 2024)
This study examines the epistemological aspects of management innovation in the context of Islamic education. In an era of rapid technological development, Islamic educational institutions face challenges to remain relevant and effective. Innovation in educational management is key to facing this change. However, such innovation needs to be based on a strong epistemological understanding to ensure that the changes made are in line with the values ​​and goals of Islamic education. This study uses a qualitative approach with a literature study method. The results show that the epistemological dimension plays an important role in shaping and directing Islamic educational management innovation. A deep understanding of the sources of knowledge, the process of acquiring knowledge, and the validity of knowledge in the context of Islam is the foundation for developing effective innovation strategies that are in accordance with Islamic principles. This study also offers recommendations for integrating Islamic epistemological perspectives into modern educational management practices.